Phenomenon Of Post Sport Career: Causes And Solution - R. Syaifullah D. Sihombing (Universitas Syiah Kuala, 2021)
People and even scholar tend to have more interest to discuss athlete who still active in athletic activities. Study concerning to post sport career is relatively smaller. Moreover, as ‘profession’ sport career is very specific comparing with others profession. The duration in which athletes involves in sport activities is quite short. Moreover, the possibilities and the number who failed in the middle career are overwhelmed. Surprisingly, only 1% of athletes who involve in competitive sport have an opportunity to reach a great attain. Hence, by using literature review approach this article trying to find out causes and solutions nay problems faced by post sport career athlete.